Gambaran Komitmen Anggota Organisasi Dalam Pelaksanaan Program Kerja Karang Taruna Talaga Mas Di Desa Cinangsi, Cibogo, Kabupaten Subang - Firdaus, Muhammad Ananta; Dani, Rian; Susilowati, Ellya (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2025)
This research is focus on the commitment of Karang Taruna members in implementing five areas of youth potential distribution as Karang Taruna work programs, namely social, cultural, religious, sports, creative economy. The method used is a descriptive method with a quantitative approach. The results of the research that has been done are that the good and very good categories dominate compared to other categories for the commitment of organizational members in implementing work programs that can be seen from the dimensions, namely the Willingness of Organizational Members in Implementing Work Programs, with a good category of 87% Willingness of Organizational Members in Implementing Work Programs, with a good category of 94% and the desire to remain/loyalty in the organization in implementing work programs with a good category of 95% Keywords: Commitment of Organization Members, implementation, Work Program